Conceptual design and selection of natural fibre reinforced composite cyclist helmet liner using an integrated approach - Maidin, Nurul Ain; Salit, Mohd Sapuan; Taha, Mastura Mohammad; Yusoff, Mohd Zuhri Mohamed (Universiti Putra Malaysia Press, 2024)
This paper describes the conceptual design phase in the product development of a natural fibre composites cyclist helmet liner, beginning with idea generation and ending with selecting the best design concept. The integrated Theory of Inventive Problem Solving (TRIZ), Biomimetic methods, and the Grey Relational Analysis (GRA) method are demonstrated in this paper. This work aims to produce nature-inspired design concepts and determine the best design concept for the composite cyclist helmet liner. Following that, four design concepts were generated using the TRIZ-Biomimetic method, and the variance of concepts was developed using a morphological chart. The GRA method was chosen as the multiple criteria decision-making tool to compare their cost and weight criteria. The design concept C1 was selected as the best design concept for the natural fibre composites of cyclist helmet liner conceptual design when the highest grey relational grade (GRG) value and rank with a value of 1.0000 satisfied the GRA method conditions. This paper demonstrates how the integrated method of TRIZ-Biomimetics-Morphological Chart and GRA helps researchers and engineers develop designs inspired by nature and select the best design concept during the conceptual design stage using a systematic strategy and justified solutions.